2001
DOI: 10.1111/j.1748-5827.2001.tb02496.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding regimens on bodyweight, composition and condition score in cats following ovariohysterectomy

Abstract: The effects of ovariohysterectomy on bodyweight, composition and condition score were evaluated in 49 cats that were fed ad libitum and 11 cats that had their food allowances controlled with the aim of maintaining a stable bodyweight. In cats fed ad libitum, bodyweight increased by an average of 31 per cent in the 12 months following ovariohysterectomy compared with 3.1 per cent over the 12 months before surgery, and this was largely due to increased body fat content. There was no difference in weight gain bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 12 publications
(4 reference statements)
7
40
1
4
Order By: Relevance
“…Similar to BW gain, HP-fed cats gained body fat mass faster than MP-fed cats and had increased BMC earlier in the study, which was likely to support increased weight gain. Changes in fat and lean mass percentages were similar to values reported by Harper et al (2001) in cats , 4 years of age (23.6% fat pre-neutering; 34.4% fat 12 months post-neutering; P , 0.002).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to BW gain, HP-fed cats gained body fat mass faster than MP-fed cats and had increased BMC earlier in the study, which was likely to support increased weight gain. Changes in fat and lean mass percentages were similar to values reported by Harper et al (2001) in cats , 4 years of age (23.6% fat pre-neutering; 34.4% fat 12 months post-neutering; P , 0.002).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 83%
“…Food intake and BW increased in all cats following ovariohysterectomy, as has been noted in other studies (Fettman et al, 1997;Harper et al, 2001;Kanchuk et al, 2003;Nguyen et al, 2004;Backus et al, 2007;Cave et al, 2007;Belsito et al, 2009). Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009).…”
Section: High-protein Diet Following Ovariohysterectomysupporting
confidence: 63%
“…14 In the present study, the mean %BF of cats with a BCS of 5 was 31.8. This value is slightly higher than has been reported 14,24 and could reflect a low activity level in the pet DSH cat population, resulting in less muscle mass and thus a higher %BF even in the lean cats, compared with physically active colony cats. This finding in inactive, indoor-confined, adult neutered cats appears similar to characteristics of humans categorized as socalled skinny fat.…”
Section: Discussioncontrasting
confidence: 52%
“…Neutered males and females have a more comparable body type than sexually intact male and female cats. 16,24 Furthermore, differences in body composition and activity level between sexually intact and neutered cats may cause a higher %BF associated with each BCS in neutered versus sexually intact cats.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents (4,18,21,81, 102) and domestic animals (26,35,58), ovariectomy consistently leads to a rapid increase in body weight and hyperphagia, and estradiol treatment reduces food intake and body weight (14,37,65,81,97). Ovariectomy rapidly increases body weight in nonhuman primates (89), and treatment of ovariectomized monkeys with estradiol has been shown to suppress food intake (24, 44).…”
mentioning
confidence: 99%